The potential of Canada's international student strategy: Evidence from the "MIT of the north" - Joel Blit; Mikal Skuterud; Ruiwen Zhang (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
A key objective of Canada's International Education Strategy (2014) isto leverage Canada's postsecondary institutions to attract and retain the world's "best and brightest" students to raise the average skill of the Canadian population and boost economic growth. However, evidence suggests that Canada's former international students experience significant labour market integration challenges, and the Strategy overlooks these challenges. The earnings disparities of former international students, and Canadian immigrants more generally, are usually interpreted as evidence of skill underutilization owing to employer discrimination against racial and ethnic minorities. Hard evidence of skill underutilization is, however, scant due to a dearth of data providing direct measures of workers' skills. Our study brings new evidence to bear on the skill underutilization hypothesis by examining a unique linkage of student records from the University of Waterloo, including students' grades, with immigration data from Immigration, Refugees, and Citizenship Canada and T1 income tax returns from the Canada Revenue Agency. UWaterloo is best known for its academic programs in computer science, mathematics, and engineering, which has earned it the moniker the "MIT of the North." Evidence that UWaterloo's international student graduates struggle in Canadian labour markets relative to their Canadian-born counterparts graduating from the same academic programs with similar academic standing provides a direct test of the skill underutilization hypothesis. The evidence also offers critical lessons on whether policy efforts to realize the full economic potential of international students are best directed at augmenting employer hiring behaviour through DEI initiatives, for example, or at improving the attraction and selection of international talent and promoting skill formation, including language training.
Keywords: 330; Migration policy; Students; Strategy; Labor market integration; Canada; Migrationspolitik; Studierende; Strategie; Arbeitsmarktintegration; Kanada